Home-based voluntary HIV counselling and testing found highly acceptable and to reduce inequalities - Michelo Charles; Mutale Wilbroad; Jürgensen Marte; Fylkesnes Knut (BMC, 2010)
Abstract Background Low uptake of voluntary HIV counselling and testing (VCT) in sub-Saharan Africa is raising acceptability concerns which might be associated with ways by which it is offered. We investigated the acceptability of home-based delivery of counselling and HIV testing in urban and rural populations in Zambia where VCT has been offered mostly from local clinics. Methods A population-based HIV survey was conducted in selected communities in 2003 (n = 5035). All participants stating willingness to be HIV tested were offered VCT at home and all counselling was conducted in the participants' homes. In the urban area post-test counselling and giving of results were done the following day whereas in rural areas this could take 1-3 weeks. Results Of those who indicated willingness to be HIV tested, 76.1% (95%CI 74.9-77.2) were counselled and received the test result. Overall, there was an increase in the proportion ever HIV tested from 18% before provision of home-based VCT to 38% after. The highest increase was in rural areas; among young rural men aged 15-24 years up from 14% to 42% vs. for urban men from 17% to 37%. Test rates by educational attainment changed from being positively associated to be evenly distributed after home-based VCT. Conclusions A high uptake was achieved by delivering HIV counselling and testing at home. The highest uptakes were seen in rural areas, in young people and groups with low educational attainment, resulting in substantial reductions in existing inequalities in accessing VCT services.